Differences in Microstructural Alterations of the Hippocampus in Alzheimer Disease and Idiopathic Normal Pressure Hydrocephalus: A Diffusion Tensor Imaging Study - Hong, Y.J. (AJNR Am J Neuroradiol, 2010)
BACKGROUND AND PURPOSE: DTI can be used to assess the degradation of WM tracts by measuring the FA and MD. Decreased FA/increased MD values in the AD hippocampus have been reported by many studies. In contrast, only a few studies reported on hydrocephalus by using the DTI technique. In elderly patients with dementia and with dilated ventricles, it is often difficult to differentiate iNPH from AD with visual measurements on MR imaging. The aim of this study was to investigate the changes of microstructural integrity of the hippocampus in iNPH by using DTI and determining whether this method could be a new diagnostic tool to differentiate iNPH from AD. MATERIALS AND METHODS: We recruited 43 participants (15 healthy controls, 15 patients with AD, and 13 patients with iNPH). The FA and MD values were measured by using the region-of-interest method in the hippocampal head, body, and tail on both sides. Clinical history, neurologic examination, and neuropsychological assessment were included. RESULTS: The FA values were the lowest in the patients with AD, the patients with iNPH, and the healthy controls in this order. The MD values were the highest in the same order. These findings were consistent in the 3 subdivisions of the bilateral hippocampal regions. Hippocampal volume was not different between patients with iNPH and AD. CONCLUSIONS: The microstructural alterations of the hippocampus were more sensitive than the volumetric changes in AD and iNPH. DTI analysis might be a useful tool for discriminating AD from iNPH.